Elevated occipital β-amyloid deposition is associated with widespread cognitive impairment in logopenic progressive aphasia. Issue 12 (14th August 2013) - Whitwell, Jennifer L; Lowe, Val J; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Kantarci, Kejal; Wille, Samantha M; Senjem, Matthew L; Murphy, Matthew C; Gunter, Jeffrey L; Jack, Clifford R; Josephs, Keith A
Abstract : Background: Most subjects with logopenic variant of primary progressive aphasia (lvPPA) have β-amyloid (Aβ) deposition on Pittsburgh Compound B positron emission tomography (PiB-PET), usually affecting prefrontal and temporoparietal cortices, with less occipital involvement. Objectives: To assess clinical and imaging features in lvPPA subjects with unusual topographic patterns of Aβ deposition with highest uptake in occipital lobe. Methods: Thirty-three lvPPA subjects with Aβ deposition on PiB-PET were included in this case–control study. Line plots of regional PiB uptake were created, including frontal, temporal, parietal and occipital regions, for each subject. Subjects in which the line sloped downwards in occipital lobe (lvPPA-low), representing low uptake, were separated from those where the line sloped upwards in occipital lobe (lvPPA-high), representing unusually high occipital uptake compared to other regions. Clinical variables, atrophy on MRI, hypometabolism on 18F-fluorodeoxyglucose positron emission tomography (FDG-PET), and presence and distribution of microbleeds and white matter hyperintensities (WMHs) were assessed. Results: Seventeen subjects (52%) were classified as lvPPA-high. Mean occipital PiB uptake in lvPPA-high was higher than all other regions and higher than all regions in lvPPA-low. The lvPPA-high subjects performed more poorly on cognitive testing, including executive and visuospatial testing, but the two groups did not differ in aphasia severity. Proportion of microbleeds and WMH was higher in lvPPA-high than lvPPA-low. Parietal hypometabolism was greater in lvPPA-high than lvPPA-low. Conclusions: Unusually high occipital Aβ deposition is associated with widespread cognitive impairment and different imaging findings in lvPPA. These findings help explain clinical heterogeneity in lvPPA and suggest that Aβ influences severity of overall cognitive impairment but not aphasia.